Kesalahan menulis kalimat pada tes HSK 3 - Sakti, Karina Fefi Laksana; Ventivani, Aiga; Muyassaroh, Lukluk Ul; I, Liliana Wida Larassari; Bima, Arya (Fakultas Sastra Universitas Negeri Malang, 2022)
A person's ability to speak Mandarin (foreign speakers) can be measured by a standard language test, namely HSK. HSK is an international standard test to measure the Mandarin language proficiency of foreign speakers, ethnic minorities in China, and Chinese people living abroad. In learning Mandarin, one of the important skills that must be mastered by Mandarin learners is writing skill. The aim of this study is to analyze the mistakes in writing Chinese sentences of students of Chinese Language Education Study Program on the HSK 3 test. The most mistakes were found in question number 75, out of 22 students, there were 16 students who answered incorrectly. The mistakes in writing Chinese sentences lies in the placement of the word 最、终于、and 在 as an adverb (副词), and the writing of the special sentence pattern "是...的".